Discovering a reenchanted world: an ecofeminist reading of Divakaruni’s The Mistress of Spices - Sofia Cavalcanti (Ilha do Desterro)
Thought of as attractive and seductive, tales of wonder have traditionally been associated with the female sphere. Often representing women as selfless healers and care-givers due to their privileged link with the natural and supernatural world, myths and legends can easily lend themselves to reinforcing gender stereotypes. This article examines the widely praised magical realist novel The Mistress of Spices (Divakaruni 1997) through an ecofeminist lens proposing it as a counter-example to the problematic representation of women and nature as passive, non-agent, and non-subject entities. Drawing from material ecocriticism and ecofeminist studies, and following a non-anthropocentric approach, the article discusses how the biosemiotics of the book contributes to the “reenchantment” (Griffin 1988) of the natural world and the subsequent empowerment of the woman protagonist. Capable of intentionality, creativity, and effectivity, both the spices and their mistress establish an interspecies bond that eventually breaks the link between gender oppression and exploitation of nature, thus enabling new forms of expression and emancipatory discourses.